Ugandan medical and health sciences interns’ infection control knowledge and practices - Adriane Kamulegeya; Alex Nninda Kizito; Hannington Balidawa (Journal of Infection in Developing Countries)
Background: We assessed the level of knowledge, attitudes, and practices of recent graduates of clinical health sciences who started their one-year internship in Uganda. Methodology: This was a cross-sectional survey responded to by 209 (response rate of 70%) new interns who started their internships  in August 2011 in different Ugandan hospitals. Validated self-administered questionnaires with knowledge, attitude, and practices questions were distributed to the participants during a two-day internship orientation organized by the national internship committee. Results:  Out of 299 subjects approached, the survey was completed and returned by 209 (70%). More nurses (51.4%) failed the questions on odds of HIV transmission after a needle stick injury compared to 23.0% and 36.4% of medical and dental graduates, respectively(χ2 = 24.06 p = 0.001). There was no difference in proportions of those who re-sheath needles. Respondents who had an encounter with positive tuberculosis history when taking clinical notes while unprotected were not more motivated to use masks (χ2 = 7.06;  p = 0.07). Nurses and dentists reported more regular hand washing before and after patient contact compared to medical doctors. Conclusion: Overall, the knowledge of infection control was not impressive and the attitudes and practices appeared to be heavily influenced by the lack of an enabling environment in training hospitals and internship hospitals. There is little likelihood of change due to internship experience except for those who go to missionary hospitals that have stricter infection control protocols. More effort must be made in teaching hospitals to encourage better infection control.